Consulting report - Bigmond mexican market entry business plan - Marin Anicama, Mónica Giuliana (Pontificia Universidad Católica del Perú, 2018)
Bigmond is a Peruvian company dedicated to the search of top executives offering a superior value proposition in the market. Given the great acceptance in Peru, the firm is keen to expand its commercial activities to Mexico to become a multinational company. The objective of the project is to develop a viable business plan for Bigmond's entry into the Mexican Executive search market. An external market analysis was carried out to identify opportunities and threats that could influence the success of the project. In addition, an industry analysis to assess Porter’s Five Forces was carried out. After identifying the key factors, a qualitative and quantitative study of the Mexican market was conducted to define the target market of the project in which Bigmond should focus. The historical development of Mexico's industries, the growth forecast, the demand for talent by sector, the provision for outsourcing services in companies, the concentration of potential companies at the regional level and the main market trends were taken into consideration for the assessment. Results showed that the target market should focus on the central region of Mexico and on the development of the technology industry in each of these four main economic sectors: Marketing and Communications, Manufacturing, and Financial Services and Construction. Within a next step opening a branch in Mexico City has been identified as the most suitable entry strategy for Bigmond. Then, the implementation plan included the marketing mix, which showed that one of the key success factors will be the development of brand equity. Finally, the financial analysis indicated a resulting economic TIR of 102.5% and a NPV of US $ 309,000. In addition, a sensitivity analysis assessed the expected market share. Findings of the nine scenarios showed an expected minimum IRR above 15% and a NPV greater than zero. This leads to the conclusion that establishing a commercial activity in the Mexican market is a feasible option with a promising outlook for Bigmond.

Bigmond es una empresa peruana dedicada a la búsqueda de altos ejecutivos con una gran propuesta de valor en el mercado. Dada la gran aceptación en el Perú, la firma tiene mucho interés en extender sus horizontes y llevar su propuesta de valor a México. El objetivo del proyecto es desarrollar un plan de negocio viable para la entrada de Bigmond al mercado de Executive search en México. Para ello, se realizó un macro análisis de mercado para identificar oportunidades y amenazas que podrían influenciar el éxito del proyecto. Además, se realizó un análisis de la industria a través de las cinco fuerzas de Porter. Luego de identificar los factores claves, se realizó un estudio cualitativo y cuantitativo del mercado mexicano para definir el mercado objetivo del proyecto en el cual Bigmond debe enfocarse. Se tomó en consideración el desarrollo histórico de las industrias de México, el pronóstico de crecimiento, la demanda de talento por sector, la disposición por los servicios outsourcing en las empresas, la concentración de potenciales empresas a nivel regional y las principales tendencias del mercado. El resultado definió que el mercado objetivo se ubica en la región central de México y debe enfocarse en cuatro principales sectores económicos: Marketing y comunicaciones, Manufactura, Servicios Financieros y Construcción, con un gran enfoque en el desarrollo de la industria tecnológica en cada uno de los sectores. A continuación, se desarrolló la estrategia de entrada que tuvo como resultado crear una sucursal en la ciudad de México. Luego, se llevó a cabo el plan de implementación través del marketing mix el cual desplegó que el principal factor clave de éxito será el desarrollo del valor de marca. Finalmente, el estudio financiero dio como resultado un TIR económico de 102.5% y un VAN de 309 mil dólares americanos, además se realizó un análisis de sensibilidad con la cuota de mercado y el crecimiento del negocio, los nueve escenarios desplegaron un TIR superior al 15% y un VAN mayor a cero. Lo cual permite concluir que el proyecto de entrada al mercado mexicano es viable y factible.
Keywords: Responsabilidad social de las empresas; Empresas de servicios; https://purl.org/pe-repo/ocde/ford#5.02.04